P. M. Scott on geese on the Wash and the Solway Firth, 1927-1933 - Boyd, Hugh (Wildfowl, 1996)
Diaries kept by Peter Scott during his wildfowling years provide useful information on the distribution and feeding habits of 5-6,000 Pink-footed Geese wintering in northwest Norfolk and southeast Lincolnshire. They also record large numbers at the east end of the Solway Firth in September, and include some notes on Barnacle and Greylag Geese in Dumfriesshire.